Peran Perguruan Tinggi Keagamaan Islam (PTKIS) Dalam Pendidikan Perspektif Gender Menuju Indonesia Emas 2045 - Aida Maqbulah; Syafruddin; Pipin Yosepin (Program Studi Manajemen Pendidikan Islam, 2024)
This paper reviews the role of Islamic Higher Education Institutions (HEIs) in gender perspective education as a key component towards Indonesia Emas 2045. Gender education involves an understanding of gender roles and human rights. HEIs have a responsibility to integrate religious values with gender education, shaping leaders who are aware of gender equality, and able to address complex social challenges. HEIs can play a major role in addressing this. By understanding the concept of gender education, integrating it in the curriculum, and involving lecturers in the delivery of gender materials, PTKIS can create an inclusive and civilised educational environment. Through gender inclusivity policies, prevention of gender-based violence, and active student participation in gender equality, PTKIS has the potential to shape a more inclusive, just, and competitive society, in accordance with the vision of Indonesia Emas 2045 that reflects the values of justice, equality, and sustainable progress.